PARTISIPASI PENYUSUNAN ANGGARAN DAN MOTIVASI KERJA TERHADAP KINERJA MANAJERIAL BANK SYARIAH - Rosydalina Putri (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This study intends to obtain empirical evidence of the effect of budgeting participation and work motivation on managerial performance. The study was implemented in all Islamic Commercial Banks in Bandar Lampung in 2020. Data was collected by questionnaire sent to the leaders and employees that are directly related to expenditures and the determination of operational costs at Islamic Commercial Banks in Bandar Lampung. Of the 68 questionnaires distributed, there were 46 questionnaires that were returned or received with a 67,64% response rate. The data obtained were processed using The 3th version SmartPLS software with test results on the parameter coefficient between participation in budgeting and managerial performance. There was a positive effect with a t-statistic value of 3.981 and significant at 0.05. The second test result on the parameter coefficient between work motivation and managerial performance has a positive effect with a t-statistic value of 22.051 with a significant level of 0.05. The conclusion from this study states that budgetary participation and motivation to work together have an influence in determining managerial performance in Islamic banking in Bandar Lampung.